2022
DOI: 10.1111/jfs.13018
|View full text |Cite
|
Sign up to set email alerts
|

Study on the effect of atmospheric and low‐pressure plasma and its combination on the microbial reduction and quality of milk

Abstract: This study is aimed to identify the effects of atmospheric and low‐pressure plasma on milk individually and in combination, as the plasma generated and applied at different conditions have variations in the effect on food. Plasma bubbling unit (200 V and 0.24 A) was used for atmospheric plasma and Dielectric Barrier Discharge discharge plasma (70 Pa) with milk passing between the electrodes was used for low‐pressure plasma. After treatment, the initial coliform load of 7.62 log CFU/ml was decreased by a maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Meanwhile, another study of the PB of milk indicated a smearing effect in the SDS PAGE profile protein bands. Therefore, it is evident that PB cannot induce a new band or eliminate the existing band but can induce intensity changes in the existing bands with respect to the given treatment intensity . The increase in the band intensities after PB could be due to the protein–protein cross-linkage and the formation of small protein fragments …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, another study of the PB of milk indicated a smearing effect in the SDS PAGE profile protein bands. Therefore, it is evident that PB cannot induce a new band or eliminate the existing band but can induce intensity changes in the existing bands with respect to the given treatment intensity . The increase in the band intensities after PB could be due to the protein–protein cross-linkage and the formation of small protein fragments …”
Section: Results and Discussionmentioning
confidence: 99%
“…Subsequently, 20 μL of these samples was blended with 5 μL of sample loading buffer within separate Eppendorf tubes, followed by 5 min of heating at 95 °C. Following this, the tube contents were subjected to a 5 min centrifugation at 10,000 rpm (RCF/G-force: 9392 g) using a cooling centrifuge (Remi: C-24 Plus; temperature 4 °C) before being loaded (15 μL) into the stacking gel wells as outlined by Manoharan et al 13 The gel electrophoresis process was then conducted at a voltage of 120 V for 120 min. After loading, the gel was subjected to a staining process lasting 12 h, followed by a destaining process lasting 12 h before gel documentation.…”
Section: Methodsmentioning
confidence: 99%
“…Later, in individual Eppendorf Tubes ® , 20 µL of these samples were mixed with 5 µL of sample loading buffer and heated for 5 min at 95°C. The contents of the tubes were then centrifuged for 5 min at 10,000 rpm (4°C) before being loaded (15 µL) into the stacking gel wells (Manoharan et al., 2022). After loading, the electric current at 120 V was supplied through the gel for 120 min.…”
Section: Methodsmentioning
confidence: 99%
“…The samples for gel electrophoresis were diluted (1:20) in distilled water according to the manufacturer's (Himedia) protocol (https://docplayer.net/35186408-Hiper-sdspage-teaching-kit.html). Later, in individual Eppendorf Tubes R , 20 µL of these samples were mixed with 5 µL of sample loading buffer and heated for 5 min at 95 • C. The contents of the tubes were then centrifuged for 5 min at 10,000 rpm (4 • C) before being loaded (15 µL) into the stacking gel wells (Manoharan et al, 2022). After loading, the electric current at 120 V was supplied through the gel for 120 min.…”
Section: Sds-pagementioning
confidence: 99%
“…However, few studies suggest direct damage in the microbial cell walls and protein leakage due to plasma species. [158][159][160] Nevertheless, based on the plasma discharge type, the mechanism of microbial inactivation will vary. Specically, the microbes present in the liquid of the thin layer will observe more direct cell wall damage than the ones present in the larger volumes.…”
Section: Dairy Productsmentioning
confidence: 99%